Community Analysis of Arbuscular Mycorrhizal Fungi in Roots of Poncirus trifoliata and Citrus reticulata Based on SSU rDNA - Peng Wang; Yin Wang (The Scientific World Journal)
Morphological observation of arbuscular mycorrhizal fungi (AMF) species in rhizospheric soil could not accurately reflect the actual AMF colonizing status in roots, while molecular identification of indigenous AMF colonizing citrus rootstocks at present was rare in China. In our study, community of AMF colonizing trifoliate orange (Poncirus trifoliata L. Raf.) and red tangerine (Citrus reticulata Blanco) were analyzed based on small subunit of ribosomal DNA genes. Morphological observation showed that arbuscular mycorrhizal (AM) colonization, spore density, and hyphal length did not differ significantly between two rootstocks. Phylogenetic analysis showed that 173 screened AMF sequences clustered in at least 10 discrete groups (GLO1~GLO10), all belonging to the genus of Glomus Sensu Lato. Among them, GLO1 clade (clustering with uncultured Glomus) accounting for 54.43% clones was the most common in trifoliate orange roots, while GLO6 clade (clustering with Glomus intraradices) accounting for 35.00% clones was the most common in red tangerine roots. Although, Shannon-Wiener indices exhibited no notable differences between both rootstocks, relative proportions of observed clades analysis revealed that composition of AMF communities colonizing two rootstocks varied severely. The results indicated that native AMF species in citrus rhizosphere had diverse colonization potential between two different rootstocks in the present orchards.